Biodiversidad de ecotipos y rangos de agresividad de Moniliophthora perniciosa, en Theobroma cacao L., y el efecto antagonista de Rizobacterias Promotoras del Crecimiento Vegetal (PGPRs'). - Auhing Arcos, Javier Andrés (2018)
Moniliophthora perniciosa, causal agent of the 'witch's broom disease' in cocoa (Theobroma cacao), presents a high genetic variability is one of the most important diseases in cocoa plantations that causes economic losses worldwide close to 70%. The information on the populations of these fungi is important to better understand the dynamics of epidemics and help the development of biological control systems, utilization of Plant Growth Promoting Rhizobacteria (PGPR), by production of secondary metabolites with proteolytic activity or antibiotics. The objective of this study was to analyze 12 isolates of the fungus obtained from different cocoa materials at their altitudinal distribution in Ecuador for the identification of intraspecific biodiversity and the ranges of aggressiveness of the ecotypes of M. perniciosa. It was carried out by grouping by morphological characters and physiological characters with respect to the degree of severity of the ecotypes of M. perniciosa and the use of molecular tools such as the Internal Transcribed Spacer (ITS) and Enterobacterial Repetitive Intergenic Consensus (ERIC-PCR). The antagonistic factor of the cellular extracts was evaluated at 15%, where the application of the extract of S. marcescens (PM3-8), P. protegens (CHA0), B. subtilis (ATCC 55405) and E. asburiae (PM3-14) significantly reduced the development of germinative tubes at 48 h and inhibited the germination of basidiospores, preventing the dikaryotization of the fungus. The joint use of these bio controllers in agriculture will offer an alternative to benefit in reducing the use of agrochemicals. Keywords: Moniliophthora perniciosa, witch's broom disease, Theobroma cacao, Biodiversity, Ecotypes, S. marcescens, P. protegens, B. subtilis y E. asburiae.